Influence of isomorphism on the institutionalization of sustainable practices in family farming cooperatives (Desenvolvimento em Questão, 2024)
Conceiving cooperativism as an element of territorial development, based on cooperatives formed by family farmers, this article presents a multi-case study. The objective was to analyze the implications of isomorphism in the institutionalization of sustainable practices in four family farming cooperatives, located in the Northwest region of Rio Grande do Sul. In this research, the concept of isomorphism by DiMaggio and Powell (2005) was used, which characterizes the occurrence of three types of this phenomenon: coercive, mimetic and normative. The research approach is qualitative, in which data was collected through in-depth interviews and non-participant observation. The results indicate that isomorphism, especially of the coercive type, proved to be an important mechanism in the institutionalization of sustainable practices, since the four cooperatives studied suffer some type of influence from other organizations, such as Health Surveillance, Emater, municipal governments and Ministry of Agriculture, Livestock and Supply. Thus, the study considers that the influence of isomorphism is a determining factor in the institutionalization of sustainable practices, as these practices contribute to family farming cooperatives reaching institutional markets and continuing their role as agents of development in the territory in which they are located.
Keywords: cooperativism; institutional theory; isomorphism; sustainable development